Study of the Colophons in the Copies of the Tibetan Medical Treatise Byu ru’i do shal by Isidanzinvangil and the Mongolian translation of Širün čimeg - Na, Rigele (Rocznik Orientalistyczny/Yearbook of Oriental Studies, 2026)
The medical treatise Byu ru’i do shal (full Tibetan title: Gso dpyad rgya mtsho las drangs pa’i phan pa nyung bsdus byu ru’i do shal zhes bya ba bzhugs so) was originally composed in Tibetan by Mongolian Gelugpa master Isidanzinvangil at the end of the nineteenth century. It was later produced as a xylograph in Tibetan and subsequently translated and copied into several Mongolian versions. The full title of the Mongolian translation is Emnekü sinjilekü-yin dalai-ača tataɣsan tusatu öčüken quriyangɣui širün čimeg. This paper is based on two sources: the Tibetan xylograph and a copy of the first translation. It provides essential background on the treatise, with a particular focus on the colophons of these two versions. By examining the historical context behind the colophon information, the paper also provides transliterations and translations of the colophons. The unique style of colophons, often preserved and repeated by authors with only minor changes, serves as a crucial tool for identifying unrecognized works. This study highlights the colophon’s value in attributing medical texts to Isidanzinvangil, offering insights for future research.